Approaching the mortality attributable to cholera-Naughty Asian in Plasencia in 1834 through the parish registers - Daniel Leno González (Universidad de Alicante, 2018)
Objective: The objective of this study is to estimate the mortality rate attributable to cholera in 1834 in Plasencia, based on absolute mortality.Method: This is an investigation that is designed as a descriptive, cross-sectional and retrospective study. Using as the main source the sacramental records of death of the five parishes in the nineteenth century in the locality, a demographic analysis is carried out. Results: We can say that cholera was the cause of an increase in the number of sick and dead, with interesting data to highlight such as: the manifestation of social inequalities, social and urban selectivity, female overmortality, etc. Conclusions: It is clear that we started with an indirect review, known and minimized other variables, such as hunger for bad harvests (impossible to isolate), the increase in mortality in those months should then obey some extraordinary cause that coexisted, and that era The disease of cholera.